Miary odległości obiektów opisanych zmiennymi symbolicznymi z wagami - Wilk, Justyna (Dissimilarity measures for probabilistic symbolic objects, 2006)
The paper presents the way how to measure distance between probabilistic symbolic objects (objects described by modal variables). Firstly there was presented an idea and the types of modal variables (with examples) and then symbolic dissimilarity measures suggested to analyze. Finally the example of matching distance between probabilistic symbolic objects was illustrated and then cluster analysis was applied.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 224-236